2021
DOI: 10.1371/journal.pone.0245636
|View full text |Cite
|
Sign up to set email alerts
|

Classification of road traffic injury collision characteristics using text mining analysis: Implications for road injury prevention

Abstract: Road traffic injuries are a leading cause of morbidity and mortality globally. Understanding circumstances leading to road traffic injury is crucial to improve road safety, and implement countermeasures to reduce the incidence and severity of road trauma. We aimed to characterise crash characteristics of road traffic collisions in Victoria, Australia, and to examine the relationship between crash characteristics and fault attribution. Data were extracted from the Victorian State Trauma Registry for motor vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In this study, women road crash admissions accounted for 18.81% compared to men (81.13%). This is similar to studies by Giummarra et al (2021) 7 in Australia and Värnild et al (2019) in Sweden, 8 where most of their reported road crash victims were men. Among the women road crash admissions, 60.04% were single.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, women road crash admissions accounted for 18.81% compared to men (81.13%). This is similar to studies by Giummarra et al (2021) 7 in Australia and Värnild et al (2019) in Sweden, 8 where most of their reported road crash victims were men. Among the women road crash admissions, 60.04% were single.…”
Section: Discussionsupporting
confidence: 91%
“…However, contrary to what was observed in this study, MMARAS reported a decrease in the number of cases for the year 2018 in the month of November. 16 It should be 7 found that crashes with no one at fault often involved poor or wet weather. Rainy or poorer weather may increase the chances of road crashes due to slippery roads and lower visibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, inclement conditions did not differentiate well between the collision classes in this study. A related analysis of the injury description for the present cohort found that weather conditions only played a direct role in a small number of collisions [ 33 ]. Moreover, while high temperatures are associated with elevated risk of motor vehicle collisions [ 49 ], these did not differ meaningfully between the collision classes.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics known to play a role in collision risk, such as road speed, vehicle speed, vehicle characteristics or other driver behaviours, were not available. A related study that analysed the text description of the injury event for the included cases showed that very people few reported such characteristics in their collision description in their TAC claim [33]. The LCA plugin for Stata, version 1.2.1 developed by Lanza et al [34], Pennsylvania State University, Pennsylvania, USA, was used to identify the probable number of collision classes, and to estimate class membership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation